Strategi Peningkatan Mutu Lembaga Pendidikan Dasar Islam Unggulan - Syihabuddin, Muhammad Arif (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2022)
This article discusses the improvement of Islamic education institutions' quality. The concept of an excellent educational institution/excellent school departs from the management process, which designs in such a way that the consistency of the vision and mission and the consistency of goals with the targets implemented in the work program by accommodating the wishes of the strategic environment referring to the specified quality measures. This study's results explain several steps to the quality of an excellent educational institution. First, realizing a professional work attitude. Second, cultivating excellent service. Third, strengthening the mission and social action. Fourth, developing empowerment functions. Fifth, building an academic atmosphere. Sixth, realizing sustainable achievements. Seventh, cultivating the main behavior. Eighth, cultivating the primacy of the atmosphere. Ninth, establishing a positive image. After the nine things that must be taken above can be realized, the next step and target are to shift the position of Islamic education institutions from a